(3fXe GdeYdheGJ GdeMGSHjI (B/s - (3GdOgQGhj, ceGd GdOjf eUWais; (3eMeO, SejQ cGeds ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3GdeaGgje GdGSGSjI dfXe GdeYdheGJ , JTZjd GdeYdheGJ aj fXGe GdeYdheGJ GdeMGSHj, OhQGJ GdYedjGJ(B- (3fXe GdeYdheGJ GdbGFeI Ydi GdMGSHGJ GdEdcJQhfjI GdeJbOeIs
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJs